Upaya Meningkatkan Hasil Belajar IPA pada Materi Perkembangbiakan Tumbuhan Melalui Pendekatan Kontekstual - Susilawati, Dede Erni (Didaktika, 2022)
Learning sciences in State Elementary School of 2 Pagerageung had low learning outcomes. This was inseparable from the learning system implemented by the teacher. This was related to the main problem to be answered in this research to what extent a contextual approach improves the science learning outcomes of plant reproduction materials in sixth-grade students of State Elementary School of 2 Pagerageung in the 2021/2022 academic year. This research was Classroom Action Research which is carried out through two cycles, namely, cycle I and cycle II. Each cycle has four stages, namely planning, implementation, observation, and reflection. The results obtained in this study were an increase in learning outcomes in science sixth-grade plant reproduction material. Through a contextual approach, there was also an increase in learning outcomes that can be seen from the initial conditions from the results of the discussion. The average value of student learning outcomes before the implementation of the action was 19% who have completed fulfilling the KKM, which increased in the first cycle to 65%, then increased again in the second cycle to 85%. The class average also increased from 73.1 to 83.7. Teachers’ activity has increased from cycle I to cycle II, marked by an increase in the average score, namely in the first cycle with an average predicate of good (3.3), then in the second cycle, it increases to a very good predicate (3.6). It can be concluded that a contextual approach can improve science learning outcomes for plant reproduction materials in grade VI students of State Elementary School of 2 Pagerageung, Tasikmalaya Regency in the 2021/2022 academic year.